Tumor Necrosis Factor Is a Therapeutic Target for Immunological Unbalance and Cardiac Abnormalities in Chronic Experimental Chagas' Heart Disease. (22nd July 2014) - Pereira, Isabela Resende; Vilar-Pereira, Glaucia; Silva, Andrea Alice; Moreira, Otacilio Cruz; Britto, Constança; Sarmento, Ellen Diana Marinho; Lannes-Vieira, Joseli
Abstract : Background . Chagas disease (CD) is characterized by parasite persistence and immunological unbalance favoring systemic inflammatory profile. Chronic chagasic cardiomyopathy, the main manifestation of CD, occurs in a TNF-enriched milieu and frequently progresses to heart failure. Aim of the Study . To challenge the hypothesis that TNF plays a key role in Trypanosoma cruzi -induced immune deregulation and cardiac abnormalities, we tested the effect of the anti-TNF antibody Infliximab in chronically T. cruzi -infected C57BL/6 mice, a model with immunological, electrical, and histopathological abnormalities resembling Chagas' heart disease. Results . Infliximab therapy did not reactivate parasite but reshaped the immune response as reduced TNF mRNA expression in the cardiac tissue and plasma TNF and IFN γ levels; diminished the frequency of IL-17A + but increased IL-10 + CD4 + T-cells; reduced TNF + but augmented IL-10 + Ly6C + and F4/80 + cells. Further, anti-TNF therapy decreased cytotoxic activity but preserved IFN γ -producing VNHRFTLV-specific CD8 + T-cells in spleen and reduced the number of perforin + cells infiltrating the myocardium. Importantly, Infliximab reduced the frequency of mice afflicted by arrhythmias and second degree atrioventricular blocks and decreased fibronectin deposition in the cardiac tissue. Conclusions . Our data support that TNF is a crucial player in the pathogenesis of Chagas' heart disease fueling immunological unbalance which contributes to cardiac abnormalities.